An evaluation of sustainability in large British companies. (March 2019) - Iqbal, Taskin; Keay, Andrew
This article undertakes an assessment of the sustainability efforts of some of the largest companies that are listed on the FTSE 100 (a share index composed of the 100 largest companies that are listed on the London Stock Exchange according to market capitalisation). It provides empirical insights into how large listed British companies are addressing sustainability and their efforts in terms of incorporating sustainability factors into their business operations. The study was based on an extended content analysis of each company's annual and sustainability reports. Our findings demonstrate that companies are trying to integrate sustainability in their business strategies even though there are variations in their efforts. There are indications that the majority of the companies have been able to embed sustainability in their strategy and operations and are now attempting to establish goals for further improvement. We found strong evidence of willingness to engage with relevant stakeholders to evaluate which sustainability issues are of importance to the particular companies and then to communicate to those relevant stakeholders the measures that have been taken to integrate sustainability in their business strategies. However, our findings also revealed areas where there is a need for further improvement such as compliance with international standards for sustainability reporting and establishment of better frameworks to enhance their sustainability efforts.